In Situ Soybean Crude Urease Calcite Precipitation (SCU-CP) untuk Perkuatan Tanah Pasir - Fauzan Raflinur Ananda; Heriansyah Putra; Erizal Erizal; Angga Prayoga; Maulina Lamuse (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2025)
Sand has low bearing capacity due to its low shear strength and lack of cohesion. Chemical improvement is more effective than physical methods for reinforcing sand, as it does not require heavy equipment. Enzyme-Mediated Calcite Precipitation (EMCP) is a chemical method that uses pure urease enzyme, but it is not economical for field applications. Therefore, the Soybean Crude Urease Calcite Precipitation (SCU-CP) method, which substitutes pure urease with soybeans, is used as a solution. This study applies SCU-CP to reinforce sand at both laboratory and field scales using Cone Penetration Test (CPT) and Unconfined Compression Strength (UCS), with variations of 1, 2, and 3 pore volumes (PV). The study began with testing sand parameters, including gradation, specific gravity, and void ratio. Treated sand samples were tested using CPT and UCS at both scales. Calcite quantification was conducted to determine the amount and distribution of calcite formed. The results show that SCU-CP increased qc values in coarse and fine sand in the CPT test, with the highest values at 3 PV being 1.28 MPa and 2.01 MPa, respectively. Laboratory UCS tests showed maximum values at 3 PV of 331.13 kPa for coarse sand and 104.38 kPa for fine sand. Field UCS tests showed values of 193.19 kPa for coarse sand and 210.84 kPa for fine sand. Calcite distribution was uniform, with actual calcite content reaching 27.66 - 34.10% of the theoretical mass.